Answer:
7x - 3
Step-by-step explanation:
3x+(4x-3)
Remove parenthesis
3x + 4x - 3
Combine like terms
3x + 4x = 7x
7x - 3
Answer:-24
Step-by-step explanation:
-3(-2) = 6 x (-4) = -24
<h3>
Answer: -2</h3>
======================================================
Work Shown:
-------------------
Explanation:
In the second step, I multiplied top and bottom by 1/x. This divides every term by x. Doing this leaves us with various inner fractions that have the variable in the denominator. Those inner fractions approach 0 as x approaches infinity.
I'm using the rule that
where k is some positive real number constant.
Using that rule will simplify the expression greatly to leave us with -2/1 or simply -2 as the answer.
In a sense, the leading terms of the numerator and denominator are -2x and x respectively. They are the largest terms for each, so to speak. As x gets larger, the influence that -2x and x have will greatly diminish the influence of the other terms.
This effectively means,
I recommend making a table of values to see what's going on. Or you can graph the given function to see that it slowly approaches y = -2. Keep in mind that it won't actually reach y = -2 itself.
You set up the problem correctly, just keep going.
Expand out your expression:
2x(3x-9) + 4x(x+13)
= 6x^2 -18x + 4x^2 + 52x
= 10x^2 +34x
Remember that the above expression is the area, so it is equal to 24.
10x^2 + 34x = 24
10x^2 + 34x - 24 = 0 (divide by 2)
5x^2 + 17x - 12 = 0
Done.